Enfacing others but only if they are nice to you - Bufalari, Ilaria; Lenggenhager, Bigna; Porciello, Giuseppina; Serra Holmes, Brittany; Aglioti, Salvatore M. (Frontiers in Behavioral Neuroscience, 2014)
Experiencing tactile facial stimulation while seeing synchronous stimuli on the face of another individual induces 'enfacement', i.e. the subjective illusory experience of ownership of the other’s face (explicit measure) and the attribution of the others’ facial features to one’s own face (implicit measure). Here we expanded previous knowledge by investigating if the tendency to include the other into one’s own representation is influenced by positive or negative interpersonal attitudes derived either from consolidated socio-cultural stereotypes or from newly acquired, short-term individual interactions with a specific person. To this aim, we tested in Caucasian white participants the enfacement with a white and a black confederate, before and after an experimental procedure inducing a positive or negative perception of each of them. The results show that the subjective experience of enfacement with in- and out-group others before and after the manipulation is similar. The bias in attributing other’s facial features to one’s own face after synchronous stroking was, instead, dependent on whether the other person was positively perceived, independently of his/her ethnicity. Thus, we show that realistic positive face-to-face interactions are more effective than consolidated racial biases in influencing the strength of self-attribution of another persons’ facial features in the context of multisensory illusions. Results suggest that positive interpersonal interactions might powerfully change the plasticity of self-other representations.